2022
DOI: 10.1093/icvts/ivac150
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the surgical Apgar score for predicting the short- and long-term outcomes in non-small-cell lung cancer patients who undergo surgery

Abstract: Objectives The surgical Apgar score (SAS) is a simple score that predicts postoperative complications based on three intraoperative valuables. The present study evaluated the association between the SAS and postoperative outcomes in non-small-cell lung cancer (NSCLC) patients who underwent surgery. Methods A total of 585 patients who underwent lung resection were enrolled in the present study. We calculated the SAS of each pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…As expected, patients with lower SAS had worse postoperative outcomes. Some previous studies have adopted different cut-off values for postoperative risk stratification [ 7 , 14 16 ]. Although our study used a cut-off value of 7, a sensitivity analysis using a cut-off value of 6 based on the study by Gawande et al [ 5 ] also confirmed the impact of SAS on postoperative outcomes (Supplemental Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, patients with lower SAS had worse postoperative outcomes. Some previous studies have adopted different cut-off values for postoperative risk stratification [ 7 , 14 16 ]. Although our study used a cut-off value of 7, a sensitivity analysis using a cut-off value of 6 based on the study by Gawande et al [ 5 ] also confirmed the impact of SAS on postoperative outcomes (Supplemental Table 2 ).…”
Section: Discussionmentioning
confidence: 99%